Crisis management and the varieties of capitalism: Fiscal stimulus packages and the transformation of East Asian state-led capitalism since 2008 - Thomas Kalinowski (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
This paper contributes to the understanding of the diversity of capitalism by combining approaches from comparative political economy and development studies, notably developmental state theory. We show that different types of capitalism react differently to global shocks and offer some support for the classic varieties of capitalism argument that external pressure leads to the reinforcement of historically evolved institutions. Moreover, we make several departures from established theories on the variety of capitalism, namely, their Eurocentric bias, their under-theorization of the role of the state, and the methodological conservative bias of institutionalist approaches. At the empirical level, this paper studies the reaction of East Asian countries (China, Japan and Korea) to the global financial crisis with a focus on fiscal stimulus packages that were implemented from 2008 to 2010. Unlike in the West, where a (short-lived) revival of Keynesianism could be observed, East Asian governments implemented large fiscal stimulus packages with strong elements of industrial policies. This paper argues that the size and character of fiscal stimulus packages can be explained by a path dependency of developmental state capitalism. In addition, the paper examines the substantial changes in the transformation from an old-style developmental state to a neo-developmental state. – – Dieses Diskussionspapier trägt zur Diskussion über unterschiedliche Spielarten des Kapitalismus bei, indem Theorieansätze aus den Bereichen Vergleichende Politische Ökonomie und Entwicklungstheorie miteinander verbunden werden. Ich stelle in diesem Papier dar, wie verschiedene Spielarten des Kapitalismus unterschiedlich auf den externen Schock der Weltfinanz- und Wirtschaftskrise seit 2008 reagiert haben. Das Papier stützt in gewissem Maße die Behauptung der Debatte über die varieties of capitalism, dass externe Herausforderungen tendenziell zu einer Stärkung historisch gewachsener institutioneller Arrangements führen. Gleichzeitig versucht der Beitrag, einige Schwachstellen der bisherigen Forschung zur Diversität von Kapitalismus zu überwinden - insbesondere den eurozentrischen Ansatz, die mangelnde Konzeptualisierung der Rolle des Staates und die zu enge Auslegung des Begriffs der Pfadabhängigkeit. Auf der empirischen Ebene untersucht dieses Diskussionspapier das Krisenmanagement ostasiatischer Länder (China, Japan und Südkorea) seit 2008. Der Fokus liegt dabei auf der Fiskalpolitik und der Implementierung von Konjunkturpaketen. Im Unterschied zum (kurzlebigen) Revival keynesianischer Nachfragepolitik im Westen lässt sich in Asien ein Rückgriff auf Elemente der Infrastruktur- und Industriepolitik beobachten. Diese Stärkung von Institutionen des klassischen ostasiatischen Entwicklungsstaates zeigt eine pfadabhängige Entwicklung an. Gleichzeitig lassen sich jedoch auch Elemente des Wandels feststellen, und das Papier beschreibt diese pfadabhängige Transformation des ursprünglichen Ostasiatischen Entwicklungsstaates in einen Entwicklungsstaat der zweiten Generation.
Keywords: 330; Comparative political economy; international political economy; developmental state; fiscal policies; varieties of capitalism; East Asia